2019
DOI: 10.1055/s-0038-1676807
|View full text |Cite
|
Sign up to set email alerts
|

The Reach and Feasibility of an Interactive Lung Cancer Screening Decision Aid Delivered by Patient Portal

Abstract: Objective Health systems could adopt population-level approaches to screening by identifying potential screening candidates from the electronic health record and reaching out to them via the patient portal. However, whether patients would read or act on sent information is unknown. We examined the feasibility of this digital health outreach strategy. Methods We conducted a single-arm pragmatic trial in a large academic health system. An electronic health record algorithm identified primary care pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…Eight articles provide support for this theory. 13 , 14 , 34 , 36 , 39 , 51 , 52 , 59 Many patients are unfamiliar with PtDAs and have no experience of using them to support their health care decisions. When explicit invitations to engage with the PtDA are sent to patients before the decision-making consultation, this acts as a prompt for the patient and increases the likelihood that they will use the PtDA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eight articles provide support for this theory. 13 , 14 , 34 , 36 , 39 , 51 , 52 , 59 Many patients are unfamiliar with PtDAs and have no experience of using them to support their health care decisions. When explicit invitations to engage with the PtDA are sent to patients before the decision-making consultation, this acts as a prompt for the patient and increases the likelihood that they will use the PtDA.…”
Section: Resultsmentioning
confidence: 99%
“… 34 For instance, Berry et al 34 found that PtDA use increased from 0% to 14% in sites that provided written material suggesting access, compared with 82% to 87% in sites in which patient care coordinators or physicians provided direct email or telephone invitations to engage. Both Dharod et al 36 and Krist et al 39 found that digital delivery of reminders and PtDAs via patient portals was a successful strategy to increase usage. Invitations that explain the purpose of the PtDA, and SDM more broadly, better prepare and “activate” patients as they help them to understand the relevance of the PtDA and their own role in decision making, resulting in increased engagement with the PtDA and in SDM discussions during consultations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study [ 51 ] of colorectal cancer screening reminders delivered via patient portal, among the 552 patients randomized to receive messages, 54% viewed the message and 9% performed a suggested web-based risk assessment tool. In a study describing the reach and feasibility of an interactive lung cancer screening decision aid delivered by patient portal, Dharod and colleagues [ 52 ] found that 86% of lung cancer screening eligible patients identified by an electronic health record algorithm to receive a patient portal message read the message, 40% then visited a web-based decision aid for lung cancer screening, and 35% completed questionnaires to determine their eligibility for lung cancer screening.…”
Section: Discussionmentioning
confidence: 99%
“…Complex eligibility criteria can discourage providers from properly identifying eligible patients and practices from creating electronic alerts, reminders, and overdue care reports. [9][10][11] Patients and clinicians are concerned about high rates of false positives and extra-pulmonary findings. 2,9,[12][13][14][15] CMS coverage requires documentation of shared decision-making prior to screening, which is time consuming.…”
Section: Introductionmentioning
confidence: 99%